StWRKY65 stimulates thermotolerance in potato (Solanum tuberosum L.) through antioxidant and photosynthetic modulation - Zhu, Xi; Duan, Xiaoqin; Luo, Junfu; Guan, Nengkang; Zheng, Haifei; Majeed, Yasir; Zou, Huafen; Jin, Hui; Chen, Zhuo; Zhang, Yu (Frontiers in Plant Science, 2025)
Heat stress severely impacts the growth and development of potato plants. However, the molecular mechanisms underlying thermotolerance, particularly the role of WRKY transcription factors (TFs), remain poorly understood. Here, we identified StWRKY65 as a heat-responsive gene in potato, demonstrating significant transcriptional upregulation under 30°C and 35°C heat stress conditions. Phylogenetic analysis classified StWRKY65 into the WRKY Group II family, revealing high evolutionary conservation with its tomato ortholog SlWRKY65. Subcellular localization confirmed its nuclear targeting. Additionally, we generated transgenic potato lines with overexpression (OE) or RNA interference (RNAi)-mediated suppression of the target gene. Under heat stress, OE lines exhibited enhanced thermotolerance, manifested through improvements in plant height, fresh/dry weights of plants and roots, tuber yield, photosynthetic efficiency, transpiration rate, and stomatal conductance. Concurrently, compared to non-transgenic (NT) controls, StWRKY65 overexpression significantly elevated the activities of antioxidant enzymes (ascorbate peroxidase [APX], catalase [CAT], peroxidase [POD], superoxide dismutase [SOD]), proline accumulation, and total chlorophyll content, while reducing malondialdehyde (MDA) and hydrogen peroxide (H2O2) levels. Conversely, RNAi lines displayed heightened heat sensitivity, impaired growth parameters, diminished antioxidant capacity, and elevated oxidative stress markers. Furthermore, StWRKY65 overexpression transcriptionally activated key antioxidant enzyme-related genes (StAPX, StCAT1/2, StPOD12/47, StFeSOD2/3, StMnSOD, StCuZnSOD1/2), whereas its knockdown produced opposing effects. This study demonstrates the pivotal role of StWRKY65 in enhancing potato thermotolerance by simultaneously boosting antioxidant defenses and maintaining photosynthetic efficiency under heat stress. As climate change intensifies thermal extremes, these findings position StWRKY65 as a valuable genetic target for developing heat-resistant potato varieties, offering a timely strategy to protect this vital crop and global food security.